Extraction and Applications of Rosmarinus (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The main objective of this research is to evaluate the antioxidant, cytotoxic, and antimicrobial efficacy of rosemary (Rosmarinus officinalis), quantify its extraction yield, and elucidate its phytochemical profile. Rosemary, also known as Rosmarinus officinalis, is native to the Mediterranean region. It belongs to the mint family and is an evergreen shrub related to basil and marjoram. Some rosemary plants can reach a height of one meter or more. Its small, grayish-green leaves resemble pine needles and have a sweet, slightly bitter aroma similar to lemon. Its flowers range in color from white to light and dark blue and bloom in the spring.A sample of rosemary was taken, dried, ground, weighed, and placed in a Soxhlet extraction apparatus. After exiting the apparatus, it was weighed, the extraction rate was calculated, and the components present in the rosemary were identified and collected by conducting phytochemical analysis using potassium hydroxide, ferric chloride, copper acetate, acetic anhydride, and concentrated sulfuric acid.Chemical laboratory experiments were carried out, revealing some substances such as flavonoids (yellow), tannins (dark green), terpenes (blue-green), and saponins. Foam was observed, but anthraquinone glycosides were not detected. Furthermore, its toxicity to stromal cells was tested using shrimp. Six samples of the extract were taken at different concentrations, and the shrimp were monitored for a full day.The bioassay demonstrated a classical dose-dependent relationship, where higher concentrations correlated with significantly increased mortality rates of the tested cells.Based on these findings, Rosmarinus officinalis shows profound therapeutic potential and is highly recommended for further pharmacological investigation against neurodegenerative disorders (e.g., Alzheimer's disease), depression, diabetes, and oncological malignancies. Due to its proven antimicrobial, anti-inflammatory, antioxidant, and hair-growth-stimulating properties, future milestones will focus on formulating this bioactive extract into functional foods and dietary supplements. Furthermore, downstream research will investigate the genetic variations within local rosemary cultivars and evaluate their direct impact on the plant's chemotypic profile and biological efficacy.